Effects of engine design and operating parameters on the performance of a spark ignition (SI) engine with steam injection method (SIM) - Gonca, Guven (ELSEVIER SCIENCE INC, 2017)
The effects of engine design and operating parameters such as equivalence ratio (ER), compression ratio (CR), cycle pressure ratio (CPR), cycle temperature ratio (CTR), bore-stroke length ratio(D/L) inlet pressure, inlet temperature, friction coefficient (FC), mean piston speed (MPS) and engine speed on the performance characteristics such as brake thermal efficiency (BTE) and brake power output (BPO) are investigated for a steam injected gasoline engine (SIGE) with a simulation model validated with experiments using a realistic finite-time thermodynamics model (FTTM). Moreover, the energy losses arising from exhaust output (EO), heat transfer (HT), friction (FR) and incomplete combustion (IC), are illustrated by using graphs. The optimum values of engine speed, compression ratio, equivalence ratio, cycle temperature ratio and pressure ratio are presented by grid curves. Also, they are called performance maps. The results showed that the performance characteristics improve with enhancing inlet pressure, cycle pressure ratio and cycle temperature ratio; with diminishing inlet temperature and friction coefficient. The BPO can be increased up to 42%, 55% and 62% by using the optimum values of cycle pressure ratio, cycle temperature ratio and inlet pressure, respectively. Also, the BTE can be increased up to 8%, 12% and 15%, by the same way. On the other hand, the performance characteristics can improve or deteriorate with respect to different conditions of compression ratio, engine speed, equivalence ratio, stroke length and mean piston speed. Therefore, the optimum values should be determined to obtain the maximum performance conditions. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Gasoline engine; Steam injection method; Otto cycle; Spark ignition engine; Finite-time thermodynamics; Performance optimization; CYCLE DIESEL-ENGINE; DEPENDENT SPECIFIC-HEATS; IRREVERSIBLE DUAL CYCLE; REDUCE NOX EMISSIONS; MILLER CYCLE; COMPRESSION RATIO; GASOLINE-ENGINE; THERMODYNAMIC ANALYSIS; OPTIMUM CRITERIA; WORKING FLUID; Engineering; Mathematics; Mechanics